Effect of uncertainty on farmers decision making: Case of animal manure use - Bert , Vermeire; Jacques , Viaene; Xavier, Gellynck (Applied Studies in Agribusiness and Commerce, 2009)
Due to the high levels of manure application and the poor use efficiency of manure, the European agriculture is held responsible for a considerable negative impact on surface water quality (Langeveld et al., 2007). This problem has emerged particularly in Western-European countries such as the UK, Belgium, The Netherlands and Denmark, facing a large expansion and intensification process in the livestock production since the 1960s (Van der Straeten et al., 2008). Policy measures related to the application of manure on the land encompass two major measures: emission rights, understood as the amount of nutrients which can be applied on the land, differentiated by crop and the N spreading calendars, whereby the manure can only be applied when the crop needs nutrients. The fundamental aim of this pillar is to maximising application rate while avoiding overfertilisation. Maximizing the application rate is related to the economic sustainability of the agricultural sector, by altering the manure surplus, while avoiding overfertilisation is imperative in enhancing ecological sustainability, by preventing nitrate leaching to surface and soil waters. For nitrate policy to meet its target, the farmers should not exceed their emission rights, however make optimal use of their emission right for manure. Consequently, the successful implementation of sink-related measures will strongly depend of the absorptive capacity of farmers towards new ways of nutrient management in general and of animal manures in particular.